Pemanfaatan Tepung Tulang Ikan Tenggiri untuk Meningkatkan Daya Terima dan Kandungan Kalsium Biskuit dan Opak Singkong - Sefanadia Putri; Ari Nugroho (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2019)
Background: Lampung Province is one of the provinces that has considerable marine fishery resource potential. Purpose: Mackerel bone flour has the potential to be developed because the mackerel fish bone meal contains high calcium. Methods: This research is a laboratory experimental study. The treatment is done by adding fish bone meal into biscuits and opaque products. Addition of fish bone meal to each product consists of 6 levels with different concentrations and 3 repetitions. Data analysis using univariate analysis and bivariate analysis using analysis of variance (Anova) test. Results: The results showed that the concentration of addition of mackerel fish bone meal most favored by Panelists on biscuit products in formula 3, namely biscuits with the addition of mackerel bone flour concentration of 5% and cassava opaque products in formula 3, namely cassava opaque with additional concentrations mackerel fish bone meal by 20%. Calcium content in formula 3 (5%) biscuits is 0.72%, cassava formula 3 (20%) is 0.131%. Conclusion: Panelists most like biscuit products with the addition of 5% mackerel fish bone flour and 0.72% calcium content, while cassava Opak is preferred with the addition of 20% mackerel fish bone meal containing 0.131% calcium.